Postpartum hemorrhage incidence and risk factors: Evidence from a multicenter study in Zhejiang Province, China - Xiaoyi Ding; Mustafe Abdi; Bingqing Liu; Yuanying Ma (PLoS ONE, 2025)
Objective Postpartum hemorrhage (PPH) is a leading cause of maternal mortality worldwide, and its risk factors vary regionally. This study assessed the incidence and determinants of PPH in Zhejiang Province, China. Methods We conducted a cross-sectional study using data from the Maternity Near Miss Surveillance System in Zhejiang Province, collected from January to December 2020. The cohort included 56,014 pregnant women at a gestational age of 28 weeks or more. PPH was defined as blood loss of ≥500 mL for vaginal deliveries and ≥1,000 mL for cesarean sections within 24 h of delivery. Logistic regression analyzed the risk factors for PPH. Results Of the pregnant women, 2,016 (3.60%) experienced PPH. The mortality rate associated with PPH was 1.74 per 100,000 live births. Significant independent risk factors included multiple births (OR 3.10; 95% CI 2.42–3.98; P < 0.01), vaginal delivery (OR 3.00; 95% CI 2.62–3.42; P < 0.01), macrosomia (OR 2.30; 95% CI 1.97–2.68; P < 0.01), hypertensive disorders of pregnancy (OR 1.79; 95% CI 1.50–2.13; P < 0.01), and a lower educational level (OR 1.20; 95% CI 1.07–1.36; P < 0.01). Conclusion The incidence and mortality rates of PPH in Zhejiang Province are low. Identified risk factors such as multiple births, vaginal delivery, macrosomia, hypertensive disorders, and lower education level can guide interventions to mitigate PPH risk.